2020
DOI: 10.1093/mnras/staa2857
|View full text |Cite
|
Sign up to set email alerts
|

The role of collision speed, cloud density, and turbulence in the formation of young massive clusters via cloud–cloud collisions

Abstract: Young massive clusters (YMCs) are recently formed astronomical objects with unusually high star formation rates. We propose the collision of giant molecular clouds (GMCs) as a likely formation mechanism of YMCs, consistent with the YMC conveyor-belt formation mode concluded by other authors. We conducted smoothed particle hydrodynamical simulations of cloud-cloud collisions and explored the effect of the clouds’ collision speed, initial cloud density, and the level of cloud turbulence on the global star format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…time) increases, especially as they approach 10 4 M . Similar behaviour is seen by Liow & Dobbs (2020) in models of cloud-cloud collisions which do not include feedback, where massive clusters contract once gravity becomes important. The results imply that variations in metallicity, dust absorption, and radiation pressure do not guarantee changes in cluster compactness, even though the H regions produced by each model are of different sizes and masses (as shown in Fig.…”
Section: Star Formationsupporting
confidence: 73%
“…time) increases, especially as they approach 10 4 M . Similar behaviour is seen by Liow & Dobbs (2020) in models of cloud-cloud collisions which do not include feedback, where massive clusters contract once gravity becomes important. The results imply that variations in metallicity, dust absorption, and radiation pressure do not guarantee changes in cluster compactness, even though the H regions produced by each model are of different sizes and masses (as shown in Fig.…”
Section: Star Formationsupporting
confidence: 73%
“…They reported the dependencies in column density for the formation of O-type stars in isolation and/or in a cluster. They suggested that 10 O stars (or a single O star) can be produced for total column density of 10 23 (10 22 ) cm −2 (see also Inoue et al 2018;Liow & Dobbs 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We use the DBSCAN algorithm (Density-Based Spatial Clustering of Applications with Noise; Ester et al 1996) -see e.g. Joncour et al (2018) for a comprehensive description of the method and its usage for observed stellar systems, and Liow & Dobbs (2020) for an application in simulations of cloud-cloud collisions. We set 5 as the minimum number of members required to define a cluster, and 𝜖 = 3 pc as the maximum neighbour separation.…”
Section: Sink Clusteringmentioning
confidence: 99%